REVISIT OF BAKASI PENISULA NIGERIA CAMEROUN RESOURCE CONFLICT - ODE AGI OKO; AWUDU SHEKARAU MASA-IBI (International Studies Journal)
The discovering of huge natural oil deposit in the waters surrounding the Bakasi Peninsular changed the good harmonious relations between Nigeria and Cameroon commencing from 1981. This scenario set in motion series of events that strained the relations between both countries that even culminated in violent conflict. The paper is set to examine the role of Border-Resource based conflict, with particular interest on how natural resources in Nigeria-Cameroun Border can influence dispute and means of managing the conflict between the two countries on border issue. The study also wishes to find out types of particular resources that was the bone in of contention and its economic values to the two border countries. It was established that the Nigerian state administered the areas commonly known as Bekasi peninsular which falls along the borders between Nigeria and Cameroun for decades peacefully. However, from 1991 the Cameroun government challenged the rights of Nigeria government over the peninsular which culminated in a suit at the International Court of Justice (ICJ) at The Hague. The study data were collected through documentation of secondary sources, including review of related historical archival records, journals, write-ups and library research built on its exiting findings. The study is concluded by recommending among others, that there is the need for inclusiveness of stakeholders in the border dispute resolutions befores the intervention of the international community following the judgment of ICJ as the terms of the Green Tree Agreement, and the need for the setting up of a joint commission for exploration of hydrocarbon in the cross-border areas, be carefully managed to douse the violent, and which will also create a platform for win win solution from both countries.